2013
DOI: 10.1177/0284185113483677
|View full text |Cite
|
Sign up to set email alerts
|

Impact of image quality, radiologists, lung segments, and Gunnar eyewear on detectability of lung nodules in chest CT

Abstract: Sensitivity for lung nodules was significantly enhanced by Gunnar eyewear (+3%), while lower image quality (40 ref mAs) had no impact on nodule sensitivity. Not using the glasses had a bigger impact on sensitivity than lowering the image quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…Another similar study found that the reduction of radiation dose between standard-dose CT and 50%-reduced-dose CT that could be achieved with acceptable image quality was up to 50%, from 15.6-21.4 mSv down to 7.8-10.7 mSv, respectively [46]. Gunnar (2013) has also reported that there was no impact upon the mean sensitivity of readers when viewing scans of lower image quality (those taken at 150 mAs compared with 40 mAs) [49]. Finally, image noise is key to determine the tube current needed to obtain the desired image quality at the prescribed noise index.…”
Section: Principles Of Ct Radiation Dose Reductionmentioning
confidence: 99%
“…Another similar study found that the reduction of radiation dose between standard-dose CT and 50%-reduced-dose CT that could be achieved with acceptable image quality was up to 50%, from 15.6-21.4 mSv down to 7.8-10.7 mSv, respectively [46]. Gunnar (2013) has also reported that there was no impact upon the mean sensitivity of readers when viewing scans of lower image quality (those taken at 150 mAs compared with 40 mAs) [49]. Finally, image noise is key to determine the tube current needed to obtain the desired image quality at the prescribed noise index.…”
Section: Principles Of Ct Radiation Dose Reductionmentioning
confidence: 99%